HUBUNGAN GAYA BELAJAR TERHADAP HASIL BELAJAR IPS KELAS V DI SD MADANI ISLAMIC SCHOOL RIAU - Saleh, Khairul; Nurainun; Amir, Zubaidah; Harpizon, Nadia Adillah (UNIB Press, 2024)
Fifth graders at SD Madani Islamic School Riau were the subjects of this research, which aimed to identify any correlation between students' preferred learning methods and their performance on social studies-related assessments. This study used a quantitative approach and a correlational research strategy. A closed questionnaire was used to get information on learning style characteristics, and documentation was employed to gather data about learning outcomes. Using a purposive sampling approach, 24 respondents, all fifth graders from SD Madani Islamic School Riau, were chosen for the study. Descriptive statistics and inferential statistics, namely the One Way Anova test, were used to evaluate the data. There were a total of 19 primary school pupils at Madani Islamic School Riau who leaned toward visual learning (79%), 3 who leaned toward auditory learning (13%), and 2 who leaned toward kinesthetic learning (8%). Students' average learning outcome scores in social studies (as shown from their final semester exam results) are 85.6 for visual learners, 88.0 for auditory learners, and 86.5 for kinesthetic learners. A significance threshold of 5% was used in the One Way ANOVA data analysis, and the result is 0.478> 0.05. So, it follows that Ha is not accepted whereas Ho is. The results show that fifth graders at SD Madani Islamic School Riau do not differ significantly in their social studies performance based on their preferred learning styles.